Characterization of transmembrane auxin transport in Arabidopsis suspension-cultured cells - Seifertová, Daniela; Skůpa, Petr; Rychtář, Jan; Laňková, Martina; Pařezová, Markéta; Dobrev, Petre I; Hoyerová, Klára; Petrášek, Jan; Zažímalová, Eva (Journal of plant physiology, 2014)
Polar auxin transport is a crucial process for control and coordination of plant development. Studies of auxin transport through plant tissues and organs showed that auxin is transported by a combination of phloem flow and the active, carrier-mediated cell-to-cell transport. Since plant organs and even tissues are too complex for determination of the kinetics of carrier-mediated auxin uptake and efflux on the cellular level, simplified models of cell suspension cultures are often used, and several tobacco cell lines have been established for auxin transport assays. However, there are very few data available on the specificity and kinetics of auxin transport across the plasma membrane for Arabidopsis thaliana suspension-cultured cells. In this report, the characteristics of carrier-mediated uptake (influx) and efflux for the native auxin indole-3-acetic acid and synthetic auxins, naphthalene-1-acetic and 2,4-dichlorophenoxyacetic acids (NAA and 2,4-D, respectively) in A. thaliana ecotype Landsberg erecta suspension-cultured cells (LE line) are provided. By auxin competition assays and inhibitor treatments, we show that, similarly to tobacco cells, uptake carriers have high affinity towards 2,4-D and that NAA is a good tool for studies of auxin efflux in LE cells. In contrast to tobacco cells, metabolic profiling showed that only a small proportion of NAA is metabolized in LE cells. These results show that the LE cell line is a useful experimental system for measurements of kinetics of auxin carriers on the cellular level that is complementary to tobacco cells.
Keywords: biologický transport; kyselina 2,4-dichlorfenoxyoctová; kyseliny naftalenoctové; Phenotype; kotyledon; listy rostlin; Naphthaleneacetic Acids; Nicotiana; Indoleacetic Acids; 2,4-Dichlorophenoxyacetic Acid; Plant Leaves; hypokotyl; Hypocotyl; Biological Transport; metabolom; kyseliny indoloctové; Cotyledon; Metabolome; Arabidopsis; buněčné kultury; fenotyp; regulátory růstu rostlin; Cell Culture Techniques; semenáček; Seedlings; tabák; Plant Growth Regulators